2021
DOI: 10.1016/j.ajogmf.2021.100360
|View full text |Cite
|
Sign up to set email alerts
|

Maternal outcomes of cesarean delivery performed at early gestational ages: a systematic review and meta-analysis

Abstract: This study aimed to report maternal outcomes of preterm (<34 weeks of gestation) cesarean delivery. DATA SOURCES: Medline, Embase, and ClinicalTrials.gov databases were searched electronically on September 1, 2020, utilizing combinations of the relevant medical subject heading terms, key words, and word variants for "cesarean delivery" and "outcome." STUDY ELIGIBILITY CRITERIA: We included only studies reporting maternal outcomes of cesarean delivery performed at <34 weeks of gestation. STUDY APPRAISAL AND SYN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Similarly, preterm CD is known to be associated with maternal complications such as infections, large blood loss, and even death, 18 probably due to surgical challenges caused by the thicker lower uterine segment that has a larger surface area of the transected myometrium. A recent review and meta‐analysis by Cerra et al reported a higher rate of intraoperative and postoperative complications in women who underwent preterm CD 19 . The described literature may explain the higher prevalence of prolonged CD in preterm deliveries in our study.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Similarly, preterm CD is known to be associated with maternal complications such as infections, large blood loss, and even death, 18 probably due to surgical challenges caused by the thicker lower uterine segment that has a larger surface area of the transected myometrium. A recent review and meta‐analysis by Cerra et al reported a higher rate of intraoperative and postoperative complications in women who underwent preterm CD 19 . The described literature may explain the higher prevalence of prolonged CD in preterm deliveries in our study.…”
Section: Discussionsupporting
confidence: 43%
“…A recent review and meta-analysis by Cerra et al reported a higher rate of intraoperative and postoperative complications in women who underwent preterm CD. 19 The described literature may explain the higher prevalence of prolonged CD in preterm deliveries in our study.…”
Section: Our Findings In the Context Of Other Observationsmentioning
confidence: 58%
“…Caesarean delivery is a primary obstetric lifesaving intervention for a mother and her newborn from pregnancy and childbirth-related complications when undertaken for medical reasons [1][2][3][4][5][6][7]. Childbirth through a surgical incision in the mother's abdomen and the uterus is known as caesarean section (CS).…”
Section: Introductionmentioning
confidence: 99%
“…However, the combined analyses of all available data on this topic do not suggest that a systematic practice of C-section is superior to vaginal delivery despite isolated reports of benefit [8, 10]. Furthermore, the maternal risks of C-section on subsequent reproductive health need to be acknowledged [27]. Our findings add novel evidence on this topic and suggest that in situations of impeding preterm delivery where a vaginal delivery can be considered, the outcomes of BPD and death or BPD do not justify the preference for delivery by C-section.…”
Section: Discussionmentioning
confidence: 99%